Use of international non-proprietary nomenclature (INN) and proprietary terms for drugs in general Hospital, Colombo (GHC) - Kuruppuarachchi, L.; Jayasinghe, K.S.A.; Sheriff, M.H.R. (Sri Lanka Medical Association, 1992)
Mandatory use of INN (or generic names) when prescribing is controvelsial. Nevertheless, use of INN for state sector should be less controversial, because only the most cost-effective preparations obtained via the State Pharmaceutical Corporation are stocked by the in-door pharmacy. Use of proprietary names (PN) under these circumstances may lead to confusion and is irrational. This study investigates the use of INN and PN for drugs by medical officers and nursing staff in selected units of ORC. A random sample of 210 patient records were studied from 12 medical wards and 3 special units. Of the entries made by doctors 79.5% were INN, while the remainder was in PN. When INN names were written by the doctor, 60% of the corresponding entries made by the nurses were in INN. An analysis of the labels in bottles containing drugs in the wards showed that 36% of the labels were in INN, 11.6% in proprietary names and 52.4% in both

Abstract : Mandatory use of INN (or generic names) when prescribing is controvelsial. Nevertheless, use of INN for state sector should be less controversial, because only the most cost-effective preparations obtained via the State Pharmaceutical Corporation are stocked by the in-door pharmacy. Use of proprietary names (PN) under these circumstances may lead to confusion and is irrational. This study investigates the use of INN and PN for drugs by medical officers and nursing staff in selected units of ORC. A random sample of 210 patient records were studied from 12 medical wards and 3 special units. Of the entries made by doctors 79.5% were INN, while the remainder was in PN. When INN names were written by the doctor, 60% of the corresponding entries made by the nurses were in INN. An analysis of the labels in bottles containing drugs in the wards showed that 36% of the labels were in INN, 11.6% in proprietary names and 52.4% in both
Sri Lanka Medical Association -105th Anniversary Academic Sessions; 1992; 29p.